2020
DOI: 10.1016/j.meegid.2020.104616
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spread across the Colombian-Venezuelan border

Abstract: Introduction Venezuela and Colombia both adopted measures of containment early in response to the COVID-19 pandemic. However, Venezuela's ongoing humanitarian crisis has decimated its health care system, and forced millions of Venezuelans to flee through its porous border with Colombia. The extensive shared border, and illegal cross-border transit through improvised trails between the two countries are major challenges for public health authorities. We report the first SARS-CoV-2 genomes from Vene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…In addition, our analyses on the geographic distribution of SARS-CoV-2 revealed significant heterogeneity, with some regions of Colombia being heavily affected, particularly after lifting restrictions on August 2020 ( Figure 2 and Supplementary Data S1 ). The most likely contributing factors influencing the high density of cases in these regions include links to travelers returning from other epidemic areas and implementation of ineffective intervention measures as well as poor social compliance [ 10 , 12 , 18 , 29 ]. Other causes include the highly porous nature of the borders with neighboring countries (Brazil and Peru)—favoring illegal migration—social inequality, and poor access to healthcare services [ 3 , 29 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our analyses on the geographic distribution of SARS-CoV-2 revealed significant heterogeneity, with some regions of Colombia being heavily affected, particularly after lifting restrictions on August 2020 ( Figure 2 and Supplementary Data S1 ). The most likely contributing factors influencing the high density of cases in these regions include links to travelers returning from other epidemic areas and implementation of ineffective intervention measures as well as poor social compliance [ 10 , 12 , 18 , 29 ]. Other causes include the highly porous nature of the borders with neighboring countries (Brazil and Peru)—favoring illegal migration—social inequality, and poor access to healthcare services [ 3 , 29 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has precluded an accurate assessment on the impact of control strategies across wide settings throughout the pandemic period. On the other hand, genomic surveillance of SARS-CoV-2 in Colombia has been restricted to a limited number of genomes sequenced to date (less than 1% of the total number of confirmed cases) [ 15 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of the interregional importations of the virus seems to be relatively limited. Empirical evidence shows that compared with the long-distance spread across regions, SARS-CoV-2 is much easier to spread between neighboring countries over short distances (22,79,80). For Southeast Asia, international travel bans were announced at a very early stage of the pandemic (76,81), but movement restrictions within the region, the focus of this research, were relatively loose (81).…”
Section: Discussionmentioning
confidence: 99%
“…However, literature on cross-border spread of COVID-19 is scarce. One of the few studies reporting on cross-border regions with regards to COVID, reported cross-border transmission despite a lockdown of the country and imposing border restrictions [ 13 ]. A British study which analysed the transmission of COVID in bordering districts in England during the first COVID wave showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Although cross-border measures are crucial to COVID-19 response [ 11 , 12 ], to our knowledge, only few studies have been published about COVID-19 transmission and challenges in border regions. One of these studies assessed cross-border transmission of the SARS-CoV-2 virus in the border regions of Venezuela with Colombia and Brazil, and reported similar genome sequences of SARS-CoV-2 despite measures in place to limit mobility, including a lockdown [ 13 ]. A recently published British study attributed pre-crisis commute to work between districts as a major cause for SARS-CoV-2 spread during the first wave of the pandemic [ 14 ], which is a scenario with similar conditions compared to the present study.…”
Section: Introductionmentioning
confidence: 99%